Distribution of Bithynia leachii (Sheppard, 1823) and Bithynia troschelii (Paasch, 1842) (Gastropoda: Bithyniidae) in the Czech Republic - Luboš Beran (Malacologica Bohemoslovaca, 2009)
This paper summarises all known data about the occurrence and distribution of Bithynia leachii (Sheppard, 1823) and Bithynia troschelii (Paasch, 1842) in the Czech Republic. Both species were already recorded from the Czech Republic in the past, but they were not distinguished. Autochthonous occurrence of both species is restricted to South Moravia; in the floodplains along the Morava River and the Dyje River where both species are very rare. Bithynia troschelii was also found in other sites situated in Bohemia and northern Moravia but these occurrences are not indigenous.